NLRP3 inflammasome activation in astrocytes restricts SARS-CoV-2 through gasdermin-D-driven IL-1β release - de Farias, Ingrid S.; Duarte-Barbosa, Márcia; Salazar, Natalia; Andreata-Santos, Robert; de Lucena, Victoria Weise L.; Maricato, Juliana T.; Gazzinelli, Ricardo T.; Janini, Luiz Mário Ramos; Bortoluci, Karina Ramalho (Frontiers in Immunology, 2026)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the third highly pathogenic coronavirus to emerge in humans in recent decades. Although primarily a respiratory virus, SARS-CoV-2 can invade the central nervous system (CNS), leading to severe neurological manifestations such as stroke, encephalopathy, and memory loss. However, the mechanisms by which neural cells control SARS-CoV-2 infection remain poorly understood. Here, we demonstrate that SARS-CoV-2 and its Nucleocapsid (N) and Spike (S) proteins induce classical NLRP3 inflammasome activation in astrocytes. Notably, astrocytes lacking NLRP3 or caspase-1 exhibit higher viral loads, indicating a crucial role of the NLRP3 inflammasome in astrocyte-mediated viral control. Similarly, gasdermin-D (GSDMD)-deficient astrocytes display increased susceptibility to infection, although their LDH release remains unaffected, suggesting that pyroptosis is not required for viral restriction. Instead, GSDMD deficiency leads to markedly reduced IL-1β secretion, and exogenous IL-1β rescues the impaired antiviral response in NLRP3-, caspase-1-, and GSDMD-deficient astrocytes. Our findings reveal that astrocytes autonomously control SARS-CoV-2 infection via the NLRP3-GSDMD-IL-1β axis, underscoring their active role in the neuroimmune response to viral infection.